ANALISIS PENGARUH KEMANFAATAN AUTOMATIC FISH FEEDER AT89S51 TERHADAP PROFITABILITAS USAHA KELOMPOK PETANI IKAN BERKAH MINA DI KABUPATEN PURBALINGGA - wika purbasari; Muh Sofi'i; Joko Purnomo (Jurnal Teknologi Informasi, Ilmu Komputer dan Manajemen, 2019)
This research is to find out whether there is a difference in the effect of the utilization of Automatic Fish Feeder AT89S51 on the profitability of the business of mina's blessed fish farmers in Purbalingga district before and after using Automatic Fish Feeder AT89S51. The location of the study was conducted in the village of Cipawon, Bukateja sub-district, Purbalingga district on July 12, 2018 until June 22, 2019 with consideration six months before and six months after the use of Automatic Fish Feeder AT89S51. Hypothesis testing in this study uses paired t test (paired sample t test) and shows that the value of sig. (2-tailed) of 0,000 <0.05 so it is said that there is a difference in the profitability of the business groups of blessed fish farmers before and after using the Automatic Fish Feeder AT89S51.